Development of the Banking Sector in the Digital Economy ("Journal "U". Economy. Management. Finance.", 2022)
The article examines the features of the development of the banking system in the context of the introduction of the digital economy. Various ways of development to improve and increase the efficiency of commercial banks and their interaction with other participants in economic relations are considered.
Keywords: banking sector; digital economy; information technologies; digital technologies; banking; banking services; banking technologies